EKSTRAKSI DNA DAUN KUMIS KUCING (Orthosiphon stamineus Benth.) KERING - Gusti Ayu Putu Intan Pandini; Made Pharmawati; Made Ria Defiani (Program Studi Biologi Universitas Udayana, 2025)
Orthosiphon stamineus Benth. is known as “kumis kucing” is one of the traditional medicinal plants widely used in Indonesia. Morphological identification of dried “kumis kucing” leaves as a herbal remedy is insufficient to prove the existence of counterfeiting practices, thus a more specific authentication method such as molecular genetic identification is required. However, before performing PCR, the selection of DNA extraction method with optimal quantity and quality is necessary. Therefore, this study aims to compare the effectiveness of the Doyle & Doyle method using CTAB, the Dellaporta method using SDS, and the Rogers & Bendich method in extracting DNA from dried “kumis kucing” leaves with the hope of providing information about the best DNA extraction method that can be used to identify the authenticity of “kumis kucing” leaves more accurately. The research method begins with sample preparation, DNA extraction, DNA quantity testing, electrophoresis, and visualization using a UV Transilluminator. Based on this research, the effective method for extracting DNA from dried “kumis kucing” leaves is the modified CTAB method (Doyle & Doyle, 1990), as it yields a high DNA concentration of 1508,33 ng/µL and has a faster processing time, taking 16 hours and 20 minutes. The visualization results show clear and thick DNA bands; however, the resulting DNA is not pure (A260/230: 1,01 and A260/280: 0,59).